The name of a person under 18 years of age in the medical records - Portillo González Armando F; Baeza Herrera Carlos (Instituto Nacional de Pediatría, 2014)
There is often a question of which is the correct way to write in the medical records, the name of people, who have not reached adulthood. We propose several alternatives that allow, within the regulatory framework, solve in a simple way this requirement for information on health.